2020
DOI: 10.1016/j.geoderma.2020.114455
|View full text |Cite
|
Sign up to set email alerts
|

Parameters influencing run-off on vegetated urban soils: A case study in Marseilles, France

Abstract: In urban areas, episodes of extreme precipitation may generate run-off floods, but urban soils are seldom considered in spatial planning documents. Our aim was to assess the infiltration of vegetated urban soils and to identify the soil parameters affecting infiltration in order to explore the potential of these soils for run-off mitigation under a Mediterranean climate with extreme precipitation episodes. We compared vegetated soils in the "urban" zone of the Marseilles' 16 th district (France) either lying o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Finally, from a hazard point of view, urban flash floods response is a combination between the spatial-temporal distribution of precipitation, local drainage system and local relief inside the city [41]. In this study, only meteorological hazards and impacts were considered, but for a wider study on urban floods, it is essential to include the different urban land uses (natural drainage) and their runoff coefficients [42,43] as well as the drainage system. However, it must be said that the study by Cortès et al [5] showed that although land uses can be very different in the Barcelona Metropolitan Area, within the ROI they are essentially non-draining ones.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, from a hazard point of view, urban flash floods response is a combination between the spatial-temporal distribution of precipitation, local drainage system and local relief inside the city [41]. In this study, only meteorological hazards and impacts were considered, but for a wider study on urban floods, it is essential to include the different urban land uses (natural drainage) and their runoff coefficients [42,43] as well as the drainage system. However, it must be said that the study by Cortès et al [5] showed that although land uses can be very different in the Barcelona Metropolitan Area, within the ROI they are essentially non-draining ones.…”
Section: Discussionmentioning
confidence: 99%
“…The test of the simple regression model above aimed to examine the extent of effects of each parameter from the five parameters which had been determined in this research on the infiltration rate. The reality was that there were still many other parameters remain that affected the infiltration rate, such as soil density, organic element content, temperature, structure, land slope, land use, and others [16][17][18][19]. The coefficient of determination (R 2 ) is an index to determine how much variability in the dependent variable can be explained by the regression model.…”
Section: Discussionmentioning
confidence: 99%
“…The second most prolific group involves the use of anthropogenic soils/Technosols as a substrate for GI development, by using municipal waste mostly for land reclamation (Barredo et al, 2020 ) and rooftops (Grard et al, 2020 ). Technosols benefit for climate change in the field of greenhouse gases management (Rees et al, 2019 ) also arouses interest in the scientific community and in the infiltration capacity for mitigation flood risk (Díaz-Sanz et al, 2020 ).…”
Section: Europe Green Strategymentioning
confidence: 99%